Pengaruh Kecerdasan Intelektual, Disiplin Kerja Dan Loyalitas Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Probolinggo - Setiawati, Rina; Widayanto, Mutinda Teguh; Pujiastuti, Agustina (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research aims to research and analyze the influence of intellectual intelligence, work discipline and work loyalty on employee performance at the Probolinggo City Personnel and Human Resources Development Agency. The sample for this research was 42 employees. Data was collected directly from respondents using questionnaires and analysis techniques using SPSS (Statistical Packages for Sosial Science (SPSS) v.22.0.) in the form of validity, reliability, classical assumption tests, multiple linear regression analysis, coefficient of determination, hypothesis testing. The research results are shown by the multiple regression equation Y = 3.401 + 0.406X1 + 0.203X2 + 0.249X3 + 2.339. Simultaneous hypothesis test results Fcount 42.165 > Ftable 2.85 with Sig. 0.000 < 0.05. This means that there is a simultaneous influence of intellectual intelligence, work discipline and work loyalty on employee performance. For the results of the partial hypothesis test, the tcount value is, X1= 6.619, X2= 2.584, four variables < 0.025. This means that there is a partial influence of intellectual intelligence, work discipline and work loyalty on employee performance. The results of the dominant hypothesis test show that the intellectual intelligence variable (X1) has a beta coefficient value that is greater than the other independent variables.